Charting the Course for a New Air Force Inspection System - Camm, Frank (RAND Corporation, 2013)
The Inspector General of the Air Force (SAF/IG) is leading an Air Force-wide effort to reduce the burden of Air Force inspection activities while also improving the quality of oversight the inspection system provides. In 2010, SAF/IG asked RAND Project AIR FORCE to join in this effort. This report presents primary data RAND collected on the Air Force inspection system and identifies effective inspection and information collection practices that the Air Force might emulate.